Higher Education in Nordic Roma and Traveller Policy Documents – Analysing Silences - Jenni Helakorpi; Ulpukka Isopahkala-Bouret (Bloomsbury Academic, 2022)
The Nordic countries have national Roma and Traveller policies (MSAH, <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00042">2018; AID, <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00002" title="Action Plan for Improvement of the Living Conditions of Roma in Oslo">2009; <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00039" title="Presentation to the European Commission of Denmark’s National Roma Inclusion Strategy">MSAI, 2011; <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00045" title="Assimilering og motstand Norsk politikk overfor taterne/romanifolket fra 1850 til i dag">NOU, 2015; Skr., <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00051">2011), which are constituted in the interplay of national and international Roma policy processes and Nordic collaboration (see Helakorpi, Lappalainen and Mietola, <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00029" title="Equality in the Making? Roma and Traveller Minority Policies and Basic Education in Three Nordic Countries">2020). However, in the Nordic countries there are no national statistics based on ethnic or racial identification since the population level statistics are based on register data in which information on ethnic and racial identification is not included. No censuses have been gathered in these countries in decades. Thus, the overall descriptions of the situation of Roma and Travellers are based on estimations and small-scale surveys. However, there are little or no reliable numerical population level estimations. Nevertheless, it is estimated that the completion of basic education and attainment to upper secondary education is distinctively lower in comparison with the rest of the population (Rajala et al., <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00049" title="Romanioppilaiden perusopetuksen tilannekatsaus 2010–2011 ja toimenpide-ehdotukset">2011; Hagatun, 2019; <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00045" title="Assimilering og motstand Norsk politikk overfor taterne/romanifolket fra 1850 til i dag">NOU, 2015; SOU, <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00052" title="Romers rätt – en strategi för romer i Sverige. [online] Stockholm">2010; <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00039" title="Presentation to the European Commission of Denmark’s National Roma Inclusion Strategy">MSAI, 2011). In addition, the current view is that the number of Roma and Travellers participating or having completed higher education (HE) is significantly smaller than the national averages (<a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00003" title="Roma, Education, and Higher Education Policies: The International Context and the Case of Sweden">Alexiadou and Norberg, 2015: 19–20; <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00045" title="Assimilering og motstand Norsk politikk overfor taterne/romanifolket fra 1850 til i dag">NOU, 2015; Hagatun, 2019; <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00048" title="Katsaus aikuisten romanien koulutustaustoihin">Rajala and Blomerus, 2015). The social dimension of HE has been firmly expressed in European policy declarations for over a decade. It rests on the idea that students accessing, participating in and completing HE at all levels should reflect the diversity of populations (London <a href="https://www.bloomsburycollections.com/book/the-roma-in-european-higher-education-recasting-identities-re-imagining-futures/ch8-higher-education-in-nordic-roma-and-traveller-policy-documents-analysing-silences#b-9781350109667-BLO-CH008_CIT00036" title="Towards the European Higher Education Area: Responding to Challenges in a Globalised World">Communiqué, 2007). The main purpose of this social agenda is to make HE institutions more inclusive and to widen access to the social privileges that HE offers.
The Roma in European Higher Education : Recasting Identities, Re-Imagining Futures